Development of the Antinuclear and Anticytoplasmic Antibody Consensus Panel by the Association of Medical Laboratory Immunologists - James, Karen (American Society for Microbiology, 2000)
The Association of Medical Laboratory Immunologists (AMLI) have developed a panel of antinuclear and anticytoplasmic antibody consensus sera that can be useful for enzyme immunoassay (EIA), Ouchterlony, and immunofluorescence assay methods. It was developed to assist in the evaluation of newly available EIA methods for the detection of autoantibodies. The panel of sera was evaluated in several clinical laboratories and a large number of laboratories owned by manufacturers of clinical autoantibody testing kits. The majority of sera performed well for the EIAs in both the clinical laboratories and the manufacturers' laboratories, but some samples had discrepant results. A major source of discrepancy is the current inability of the EIA results to be directly compared in a quantitative way as no standardization exists. The evaluation demonstrated lower sensitivity of detection by the Ouchterlony method. The limited evaluation of the sera with immunoblotting and Western blotting did not show good agreement with other methods. Further work must be done to standardize blotting methods prior to their use in routine clinical testing. The sera are now available to vendors and clinical laboratories for use in the detection of SS-A, SS-B, Sm, U1-RNP, Scl-70, Jo-1, double-stranded DNA, and centromere antibodies. The availability of the consensus sera will help evaluate and improve the EIA methods currently being used.